Loop A Is Critical for the Functional Interaction of Two Beta vulgaris PIP Aquaporins - Jozefkowicz, C. (2013)
Research done in the last years strongly support the hypothesis that PIP aquaporin can form heterooligomeric assemblies, specially combining PIP2 monomers with PIP1 monomers. Nevertheless, the structural elements involved in the ruling of homo versus heterooligomeric organization are not completely elucidated. In this work we unveil some features of monomer-monomer interaction in Beta vulgaris PIP aquaporins. Our results show that while BvPIP2;2 is able to interact with BvPIP1;1, BvPIP2;1 shows no functional interaction. The lack of functional interaction between BvPIP2;1 and BvPIP1;1 was further corroborated by dose-response curves of water permeability due to aquaporin activity exposed to different acidic conditions. We also found that BvPIP2;1 is unable to translocate BvPIP1;1-ECFP from an intracellular position to the plasma membrane when co-expressed, as BvPIP2;2 does. Moreover we postulate that the first extracellular loop (loop A) of BvPIP2;1, could be relevant for the functional interaction with BvPIP1;1. Thus, we investigate BvPIP2;1 loop A at an atomic level by Molecular Dynamics Simulation (MDS) and by direct mutagenesis. We found that, within the tetramer, each loop A presents a dissimilar behavior. Besides, BvPIP2;1 loop A mutants restore functional interaction with BvPIP1;1. This work is a contribution to unravel how PIP2 and PIP1 interact to form functional heterooligomeric assemblies. We postulate that BvPIP2;1 loop A is relevant for the lack of functional interaction with BvPIP1;1 and that the monomer composition of PIP assemblies determines their functional properties. © 2013 Jozefkowicz et al.